Use of Chalcogenide-Semiconductor-Sensitized Titania to Directly Charge a Vanadium Redox Battery - Tatiana Santos Andrade; Anastasios Keramidas; Panagiotis Lianos (Nanomaterials, 2020)
Unmediated charging of a battery using solar radiation is a very attractive project of solar energy conversion and storage. In the present work, solar energy was converted into electricity using a photocatalytic fuel cell operating with a chalcogenide-semiconductor-sensitized nanoparticulate titania photoanode and an air-cathode functioning by oxygen reduction. This cell produced sufficient energy to directly charge a vanadium redox battery functioning with a VOSO4 electrolyte and carbon paper electrodes. The whole system is characterized by ease of construction and simplicity of conception; therefore, it satisfies conditions for practical applications.